The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/agronomy12123209
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Detection Method for Phenotyping Pods in a Soybean Population Based on an Improved YOLO-v5 Network

Abstract: Pod phenotypic traits are closely related to grain yield and quality. Pod phenotype detection in soybean populations in natural environments is important to soybean breeding, cultivation, and field management. For an accurate pod phenotype description, a dynamic detection method is proposed based on an improved YOLO-v5 network. First, two varieties were taken as research objects. A self-developed field soybean three-dimensional color image acquisition vehicle was used to obtain RGB and depth images of soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…mAP is used to evaluate the performance of object detection models, particularly in multi-class object detection, measuring the model's accuracy across different categories while considering class imbalances. The formulas defining these metrics are presented in equations ( 9)- (11), where P denotes precision…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…mAP is used to evaluate the performance of object detection models, particularly in multi-class object detection, measuring the model's accuracy across different categories while considering class imbalances. The formulas defining these metrics are presented in equations ( 9)- (11), where P denotes precision…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…ASPP) module to improve the detection of weak and weak pod targets [23]. The p of the improved YOLOv5 model increased by about 6%, and the precision of POD in the 200 soybeans population reached 88.14%.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…It was found that the F1 score of the improved Yolov4-Tiny-tea model was 12.11, 11.66 and 6.76 percentage points higher than that of the YOLOv3, YOLOv4 and YOLOv5l network models, respectively [22]. Fu et al introduced the channel attention-asymmetric spatial pyramid pool (CA-ASPP) module to improve the detection of weak and weak pod targets [23]. The precision of the improved YOLOv5 model increased by about 6%, and the precision of POD number in the 200 soybeans population reached 88.14%.…”
Section: Introductionmentioning
confidence: 99%
“…If automatic picking of waxberry is to be realised, the critical tasks are waxberry target detection and spatial 3D localisation. In other words, a good detection algorithm equipped with a RGB-D or depth camera can complete the spatial localisation of waxberry fruits [4,5]. Therefore, this paper focuses on the target detection algorithm and suggests relevant improvement suggestions to lay the foundation for subsequent waxberry localisation.…”
Section: Introductionmentioning
confidence: 99%